The daily lives of adolescents with an autism spectrum disorder: Discretionary time use and activity partners - Orsmond, Gael I. (2011)
This study explores the daily lives, particularly discretionary time, of adolescents with an autism spectrum disorder (ASD). We describe the activities and activity partners of adolescents, the factors associated with their discretionary time use, and the impact of time use on their autism symptoms. Mothers of 103 adolescents with an ASD completed two 24-hour time diaries to describe their adolescent’s activity participation during the third wave of a longitudinal study. Adolescents with an ASD spent considerable time in discretionary activities, with watching television and using a computer as the most frequent activities. They most frequently spent discretionary time alone or with their mothers. They spent little time engaged in conversations or doing activities with peers. Age, gender, the presence of intellectual disability, severity of autism symptoms and maladaptive behaviors, the number of siblings, maternal education, marital status, and family income were associated with adolescent time use. Notably, greater time spent in conversation and reading predicted future decreases in severity of social impairment. The way that adolescents with an ASD spend their free time may have implications for their development and the course of their autism symptoms.